Evaluating the Implementation of Nonformal Education Policy in Indonesia: Challenges in Equality and Vocational Programs - Muta’alimah Muta’alimah; Eko Handoyo; Fathur Rokhman (STIT Ahlussunnah Bukittinggi, 2026)
Nonformal education in Indonesia plays a strategic role as a complement, supplement, and substitute for formal education in supporting equitable access to education. This study aims to analyze the implementation of nonformal education development policies in Indonesia by focusing on equality education programs and course and training institutions. This study employed a qualitative method with a content analysis approach through the examination of various regulations, policy documents, and related literature, ranging from Law Number 20 of 2003 to recent educational policies. The findings indicate that the implementation of nonformal education policies has contributed to increasing educational participation and reducing illiteracy rates. However, the effectiveness of policy implementation still faces several challenges, including limited budget allocation compared to formal education, inadequate quality of facilities and infrastructure in Community Learning Activity Centers, and disparities in instructor quality across regions. This study emphasizes the importance of strengthening governance, expanding partnerships with the industrial sector, and modernizing vocational-based curricula in order to enhance the responsiveness of nonformal education toward the challenges of economic disruption and unemployment in Indonesia.